Einfluss der Boden-Vegetation-Atmosphären Wechselwirkungen auf die dekadische Vorhersagbarkeit des Westafrikanischen Monsuns - Breil, Marcus (Wissenschaftliche Berichte des Instituts für Meteorologie und Klimaforschung des Karlsruher Instituts für Technologie, 2015)
In this work, the influence of the interactions between the soil, the vegetation and the atmosphere on the variability of the West African Monsoon is investigated. Therefore climate simulations with the regional climate model COSMO-CLM, coupled to two different Soil-Vegetation-Atmosphere-Transfer Models, are performed. Based on the simulation results sensitive processes in the West African Monsoon system are identified and their impact on its decadal variability is evaluated.